MENINGKATAN HASIL BELAJAR SISWA KELAS XI IA2 DENGAN MENGGUNAKAN STRATEGI EVERYONE IS A TEACHER HERE PADA PEMBELAJARAN KIMIA MATERI HIDROLISIS GARAM (Suatu Penelitian Tindakan Kelas di SMA Negeri 4 Gorontalo TP 2008/2009) - Santi Mekar, Wa Ode; Paputungan, Mardjan; Ischak, Netty (Jurnal Entropi, 2009)
This research is action classroom research which done at the even semester 2008/2009 academic year. The subject of the research is consisting of 30 students. Which are 7 of them are men are 23 students are women. The research divided in to two cycles that involved by one teacher as an observer. The aim of this research is to increase student achievement at the chemistry subject, salt hydrolysis material by using everyone is a teacher here strategy. The data of this research are collected by observed the teacher and the students activity while the process of teaching and learning is walking also the result of students study that collected through test. The criteria of researchs success is shown by the 80 go 90 of students 6,8, also, the observation that teacher and the students activity get 75%. The result of the research shown that the learning activity that using everyone is a teacher here strategy can increase the students achievement it can be seen by the result the students that get score more than 6, 8 or as 90%.